(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2025)
Ocimum basilicum L. (common basil) is one of the most widely used plants in the Lamiaceae family, used in the food industry and in traditional and modern medicine. The plant is rich in essential oils, phenolic compounds, flavonoids, and vitamins, which contribute to its antioxidant, anti-inflammatory, antimicrobial, cardioprotective, and metabolic properties. This review article summarizes the botanical characteristics, chemical composition, and pharmacological activity of O. basilicum L. and discusses its potential use in pharmaceuticals and preventive medicine.